Ré-enchanter le monde. Une approche du magicien et de l’artiste dans Le Magicien d’Alphonse Esquiros - Ana Alonso (Çédille: Revista de Estudios Franceses, 2018)
Le Magicien by Alphonse Esquiros is considered to be a masterpiece of Romantic Literature, but it didn’t generate much interest amont its contemporaries. Modern specialists haven’t studied it largely. That’s why essays on its characteristics and innovation are needed. The aim of this paper is, first of all, to offer a contextualization of Esquiros’ work. The author was a member of the « petits romantiques » group and occupied a marginal place in the Romantic Movement. The study also points to the elements that make Le Magicien a heterodox novel, both for its defense of hidden science and for the open character of its narrative technique that allows for multiple interpretations. The paper continues with a detailed analysis of the characters played by Stell and Ab-Haked and traces the parallels between the sculptor and the magician to establish the ambitions and evolution in their search for Beauty and Knowledge, main guidelines of their lives. Based on these characters, Esquiros’ novel extrapolates to the XVIth Century his own romantic vision of the artist in the XIXth Century and promotes the fascination with magic as a way of reenchanting the world.